Impact of Nikshay Poshan Yojana on tuberculosis outcomes: preliminary evidence from eastern India - T., Anupama; Narain, Smiti; Priyadarshini, Megha; Mitra, Anindya; Prasad, Ranjit; Pathak, Rajeev Ranjan (International Journal Of Community Medicine And Public Health, 2023)
Background: National TB programme of India implemented Nikshay Poshan Yojana (NPY) through direct benefit transfer (DBT) in April 2018. This is to address the dual evils of under nutrition and unfavourable outcomes among tuberculosis patients in the country. This study aimed to understand the impact of Nikshay Poshan Yojana (NPY) through direct benefit transfer (DBT) on the outcomes of notified TB patients from the Indian state of Jharkhand for the year 2019. Methods: This was a retrospective cross sectional descriptive study using secondary data obtained from Nikshay web portal for the Indian state of Jharkhand for the year 2019. State level data on TB notification and NPY DBT scheme was downloaded in excel format and analysed using Excel 2016 version. Results: The study found higher odds (odds ratio 3.14, 95% CI: 2.97, 3.33; p value <0.00001) of having successful outcomes, among those who received at least one instalment of NPY. The risk of lost to follow up (LTFU) was 2.44 times (95% CI: 2.2-2.8, p value: 3.9×10-43) higher among those who did not receive any DBT payments as compared to those who received at least one DBT instalment. Conclusions: The ‘individual and health system enablers’ have a crucial role to play in successful TB treatment outcomes than NPY. However, LTFU rate reduces significantly with timely payment of NPY. This would facilitate improved treatment adherence and thus a favourable outcome.